2020
DOI: 10.1098/rsta.2020.0185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of shock wave signatures at millimetre wavelengths from Bifrost simulations

Abstract: Observations at millimetre wavelengths provide a valuable tool to study the small-scale dynamics in the solar chromosphere. We evaluate the physical conditions of the atmosphere in the presence of a propagating shock wave and link that to the observable signatures in mm-wavelength radiation, providing valuable insights into the underlying physics of mm-wavelength observations. A realistic numerical simulation from the three-dimensional radiative magnetohydrodynamic code Bifrost is used to interpret changes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The dataset (also appeared in Wedemeyer et al [66] and Eklund et al [90]) samples a relatively quiet area at solar disc centre, with a few small network patches of opposite polarities, mostly located towards the top of the FOV, but also with some weaker magnetic patches located close to the centre of the FOV (as seen in the HMI magnetogram). These are observed as excess brightness temperatures in ALMA’s Band 3 images.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The dataset (also appeared in Wedemeyer et al [66] and Eklund et al [90]) samples a relatively quiet area at solar disc centre, with a few small network patches of opposite polarities, mostly located towards the top of the FOV, but also with some weaker magnetic patches located close to the centre of the FOV (as seen in the HMI magnetogram). These are observed as excess brightness temperatures in ALMA’s Band 3 images.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In particular, Eklund et al [41] found signatures of shock-wave events in Band 3 (2.8–3.3 mm) observations from December 2016, coming to the conclusion that there are numerous small-scale dynamic structures with lifetimes of 43–360 s present in the ALMA field of view (FOV), with excess temperatures of more than 400 K and a correlation between their occurrence and the magnetic field strength. Characterization of such events at millimetre wavelengths has also been studied in detail from numerical simulations [42]. Nindos et al [40] presented a survey of transient brightenings with a mean lifetime of 51.1 s in ALMA Band 3 data observed in March 2017, which show light curves such that their origin is strongly suggested to be thermal, meaning that the observed brightness temperature variations are indeed caused by variations of the gas temperature and not other effects such as optical depth variations.…”
Section: Introductionmentioning
confidence: 99%
“…We analyse coronal oscillations in the numerical simulation of magnetic enhanced network spanning from the upper convection zone to the corona (Carlsson et al 2016) using 3D radiation MHD code Bifrost (Gudiksen et al 2011). This simulation was previously used to analyse the oscillatory behaviour of chromospheric fibrils by Leenaarts & Carlsson (2015) and to study signatures of propagating shock waves by Eklund et al (2021).…”
Section: Numerical Modelmentioning
confidence: 99%